TASKS OF SITUATIONAL ANALYSIS IN PSYCHOLOGY OF MANAGEMENT - Aripova N., (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
This article is an invitation to a discussion about the meaning and content of management in the modern world and the search for a new management paradigm in the 21st century. The challenge to modern management comes from the nature of the forces, changes and processes taking place in the world. The tasks of situational analysis are proposed as effective ways to determine the factors affecting the development of the organization and the place occupied by the organization in the general economic space.